Association among University Students' Motivation, Resilience, Perceived Competence, and Classroom Climate from the Perspective of Self-Determination Theory - Manuel Sanchez-De Miguel; Aintzane Orkaizagirre-Gomara; Andrea Izagirre-Otaegi; Iker Badiola; Francisco Javier Ortiz de Elguea-Díaz; Ainara Gomez-Gastiasoro; Alberto Ferriz-Valero; Marios Goudas (MDPI AG, 2023)
Self-determination theory (SDT) suggests that motivation can interact with resilience and perceived competence. The climate-related characteristics of the classroom can influence student motivation. This study aimed to evaluate the associations between the differentiated motivation of theoretical and practical teaching, resilience, and perceived competence, considering the number of students per class and the profiles of the lecturers. A total of 789 students participated (mean age = 19.31; SD = 3.37) from Psychology, Nursing, and Education degrees from different Spanish universities. The BRS (resilience), PCNS (perceived competence), and PLOC-U (university student motivation) questionnaires were used with a new scale designed ad hoc to measure motivation in practical teaching. Student-to-class ratios and different levels of teaching experience were also recorded. A test-retest design was used to verify the stability of the measures before and after the examination of the subjects. Intrinsic motivation in practical teaching was significantly associated with resilience (r = 0.09, p < 0.03) and perceived competence (r = 0.23, p < 0.01), and in theoretical teaching, it was associated only with perceived competence (r = 20, p < 0.01). The factorial analysis of the new subscale of the PLOC-U for the measurement of motivation in practical teaching presented a good fit and reliability (α = 0.60 to 0.84) in the five factors. Test-retest analyses revealed good temporal stability. Students in small groups with more experienced lecturers scored higher on intrinsic motivation, particularly in practical classes. The stable and reliable measurement of the different types of student motivation allows their analysis and association with other variables of interest in university education, which could lead to significant improvements in teaching planning.